Thermal simulation of the cooling down of selective laser sintered parts in PA12. Issue 7 (12th October 2018) - Li, Xiaopeng; Van Hooreweder, Brecht; Lauwers, Wout; Follon, Bavo; Witvrouw, Ann; Geebelen, Kurt; Kruth, Jean-Pierre
Abstract : Purpose: The cooling process of polymer components fabricated by selective laser sintering (SLS) plays a vital role in determining the crystallinity, density and the resultant properties of the produced parts. However, the control and optimization of the cooling process remains challenging. The purpose of this paper is to therefore investigate the cooling process of the SLS fabricated polyamide 12 (PA12) components through simulations. This work provides necessary fundamental insights into the possibilities for optimization and control of this cooling process for achieving desired properties. Design/methodology/approach: The thermal properties of the PA12 powder and SLS fabricated PA12 components including density, specific heat and thermal conductivity were first determined experimentally. Then, the finite element method was used to optimize a container (a cuboid aluminum box where PA12 parts are built by the SLS) geometry in which the SLS parts can cool down in a controlled manner. Also, the cooling parameters required for maximum temperature homogeneity and minimum cooling time were determined. Findings: Two different approximations in the finite element (FE) model were used and compared. It was found that the approximation which considers powder as a solid medium with porous material properties gives better results as compared to the approximation which treats powder as a collection of air and particles with solid material properties. The results also showed that the geometry of the containers has an important influence on the cooling process of the SLS fabricated PA12 components regarding temperature homogeneity and cooling time required. A container with a small width, long length and high height tends to result in a more homogenous temperature distribution during the cooling process. Originality/value: Thermal constants of PA12 powder and parts were accurately determined as a starting point for numerical simulations. The FE model developed in this work provides useful and necessary information for the optimization and control of the cooling process of the SLS fabricated PA12 components and can thus be used for ensuring high-quality products with desired component properties.